Life-cycle assessment of compressed bricks using Cameron Highlands reservoir sediment as primary material - Ong C.-F.; Ean L.-W.; Lau S.-H.; Tan J.-H. (EDP Sciences, 2023)
Disposal of dredged sediments has recently been linked to environmental and health issues, rather than bringing any economic value to the country. Furthermore, the overexploitation of clay for brick production is destructive to the environment. Hence, it is essential to develop a decisive method to minimize the land and water pollution resulting from improper disposal as well as lessening the consumption of natural resources in the brick production. The key objective of this study is to identify environmental impacts of compressed bricks using Cameron Highlands reservoir sediment to replace clay in the compressed brick. The life cycle assessment is conducted in a cradle-to-gate manner. This study also presents the avoided process of recycled sediments in the life cycle assessment. The damage categories are quantified in terms of human health, ecosystem and resource availability by using ReCiPe Endpoint indicators. According to the results of the life cycle assessment, the compressed sediment brick is favourable from an environmental perspective. In comparison to compressed clay brick, the compressed sediment brick offers promising options for the long-term because it contributes high environmental performance among all the impact and damage categories assessed in this study. The Authors, published by EDP Sciences.